GOOD GOVERNANCE DALAM PENGELOLAAN ZAKAT (Studi Kasus Pada Badan Amil Zakat Nasional Kota Padang) - , AL ANHAR ([Yogyakarta] : Universitas Gadjah Mada, 2013)
BAZNAS city of Padang is one of the public sector organizations in the city of Padang and established by the Government of Padang. BAZNAS Padang City is required to manage the already collected zakat funds professionaly, trustworthy, transparently and accountable. the resent data show that the collection of the zakat funds, infaq and shadaqah by Baznas kota Padang in 2011 has reached Rp. 15.660.277.182. The management activity in zakat fund must be audited by a public accountant team. Previous data in community it was found that the management for collecting the fund by Baznas Padang City has never been audited and published by accountant public team. The purpose of this research is to find out why the application of the principles of transparency and accountability has not been applied by Baznas of Padang city. This research uses descriptive qualitative approach method. The Data collected is the primary and secondary data. Primary Data were obtained directly from respondents, while secondary data are obtained indirectly from documents that are relevant to the theme of research. The technique of collecting data through fieldwork and library studies through interviews, observation and documentation. The Data collected was analyzed with a qualitative descriptive techniques. Transparency and accountability are two concepts for the realization of good governance in the management of zakat. Transparency is the principle which guarantees access or freedom for everyone to obtain information. Accountability is a measure of whether the zakat funds have been used appropriately and according to its purpose. If these principles have been applied in a good manner, it will be able to manifest the good governance in the management of zakat. The result of this study shows that the principle of transparency and accountability in the Management of zakat funds by Baznas Padang City have not been implemented properly, this is due to the fact that the principle of transparency and accountability have not been implemented yet, it was found by measuring the process of transparency rate, the rate of easiness in understanding the rule and procedure of zakat management, getting access to the information and standardized complement mechanism that can be used by the related stakeholder. Whereas the accountability of principle can be seen from the existence of zakat management services, the explicit decision making and which are available for each citizen, accourate and completeness of the information, aim of explanation of policy which is adopted and communicated, the feasibility and consistency and dissemination of information about a decision. The applications of transparency and accountability principle really influence the manifestation of good governance in Zakat management by Baznas Padang City. Therefore the easiness of accessing information is really needed by the public or related stakeholders in zakat management and the report of zakat management which is audited by the public accountant and must be able to be acces openly and accepted by the govermance, DPRD and society, specially for Muzakki and Mustahid Zakat.